Bearing witness : memories of Arkansas slavery : narratives from the 1930s WPA collections - Lankford, George E., 1938- (University of Arkansas Press, 2006)
George Lankford is an emeritus professor of folklore at Lyon College. He is the author of numerous articles on southern folklore.